Taxpayer Compliance Through Internet Understanding as a Moderating Variable: Implementation of E-Filing, E-Billing and E-Registration Administration Systems - Rahma, Nadratur; Fitri, Hasmaynelis; Putra, Waldino; Nadia, Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
The level of taxpayer compliance that is still not optimal can be seen from the recent few years ofalow state tax revenues. The purpose of this study was to determine the effect ofaimplementing e-filing, e-billing andae- registration administrative systems on individua taxpayer compliance with internet understanding as a moderating variable. The research data were obtained from questionnaires (primary data) which were distributed to individual taxpayers at the Padang Satu Pratama Tax Service Office. Sampling using simple random sampling technique as many as 100 respondents. The data is processed using SPSS 23. The results of this study state that the application ofaE-filing, E-billing and the E-registration Administration System have an effect on Taxpayer Compliance. Understanding the Internet is able to moderate the effect ofaimplementing E-filing, E-billing and the E-registration Administration System on Taxpayer Compliance.